A compact modified hexagonal slot antenna for wideband applications. Issue 6 (18th August 2018) - Gangwar, Som Pal; Gangwar, Kapil; Kumar, Arun
ABSTRACT: This paper explains the design and analysis of modified hexagonal slot antenna for wideband applications. The proposed antenna is fabricated on FR-4 substrate. On one side of square substrate, a square patch is printed and one hexagonal slot and six circular slots are etched. On the other side of the substrate, a rectangular microstrip line is printed to feed the antenna. High-frequency structure simulation (HFSS) software is utilized to optimize the different antenna parameters. The simulated and measured results are compared, and these are in good agreement. The proposed design and feeding technique allows the antenna to operate within the frequency range of 2.16–3.42 GHz with the fractional bandwidth of 45.16%. The broadsided gain of proposed radiator is more than 2.6 dBi. The proposed antenna is quite appropriate for IMT (2.3–2.4 GHz), Bluetooth (2.4–2.5 GHz), WLAN (2.4–2.484 GHz), and WiMAX (2.5–2.69 GHz) applications.